Functions - understand how to do them, including the hard ones

What is a function?

In primary school when maths was more pictures and colouring and less fear and anxiety, you may have come across something like this:

A function made fun. It adds 10 to any number that goes into it and outputs the result.

Now, sadly we don’t get the fun robot anymore, instead we get something that looks like this:

f(x) = x + 10

That is the maths way to write what’s happening in the picture above.

It means that whatever x is, add 10 to it. X is the input.

If we want to input 5 we can write:

f(5) = 5 + 10

f(5) = 15

So basically we replace x with 5 and then work it out.


Example 1: Evaluating a Function

Given the function:

f(x) = 2x + 5

Find:

  • f(3)
  • f(-2)

Solution:

Finding f(3):

Substituting x = 3 into the function:

f(3) = 2(3) + 5

= 6 + 5

= 11

So, f(3) = 11.

Finding f(-2):

Substituting x = -2 into the function:

f(-2) = 2(-2) + 5

= -4 + 5

= 1

So, f(-2) = 1.

Example 2: Evaluating a Quadratic Function

Given the function:

f(x) = x² - 3x + 2

Find:

  • f(4)
  • f(-1)

Solution:

Finding f(4):

Substituting x = 4 into the function:

f(4) = (4)² - 3(4) + 2

= 16 - 12 + 2

= 6

So, f(4) = 6.

Finding f(-1):

Substituting x = -1 into the function:

f(-1) = (-1)² - 3(-1) + 2

= 1 + 3 + 2

= 6

So, f(-1) = 6.


Here are some practice questions

GCSE Functions Quiz

 

Composite Functions:

Functions can also be combined.

You can put one function inside another.

Example: Composite Functions

Given the functions:

f(x) = 2x + 3 and g(x) = x^2 - 1,

Find f(g(x)) and g(f(x)).

Solution:

Finding f(g(x)):

f(g(x)) means we substitute g(x) into f(x):

f(g(x)) = f(x^2 - 1)

Since f(x) = 2x + 3, we replace x with x^2 - 1:

f(x^2 - 1) = 2(x^2 - 1) + 3

= 2x^2 - 2 + 3

= 2x^2 + 1

Finding g(f(x)):

g(f(x)) means we substitute f(x) into g(x):

g(f(x)) = g(2x + 3)

Since g(x) = x^2 - 1, we replace x with 2x + 3:

g(2x + 3) = (2x + 3)^2 - 1

Expanding the square:

= 4x^2 + 12x + 9 - 1

= 4x^2 + 12x + 8

Final Answers:

f(g(x)) = 2x^2 + 1

g(f(x)) = 4x^2 + 12x + 8

AQA Exam-Style Questions on Functions

AQA Exam-Style Questions on Functions

1. A function \( f(x) \) is defined as:

\[ f(x) = 2x^2 - 3x + 4 \]

(a) Find \( f(5) \).

(b) Solve \( f(x) = 10 \) for \( x \).

Solution:

(a) Finding \( f(5) \)

Substituting \( x = 5 \) into the function:

\[ f(5) = 2(5)^2 - 3(5) + 4 \]

\[ = 50 - 15 + 4 = 39 \]

Answer: \( f(5) = 39 \)

(b) Solving \( f(x) = 10 \)

\[ 2x^2 - 3x + 4 = 10 \]

Rearranging:

\[ 2x^2 - 3x - 6 = 0 \]

Using the quadratic formula:

\[ x = \frac{-(-3) \pm \sqrt{(-3)^2 - 4(2)(-6)}}{2(2)} \]

\[ = \frac{3 \pm \sqrt{9 + 48}}{4} \]

\[ = \frac{3 \pm \sqrt{57}}{4} \]

Answer: \( x = \frac{3 \pm \sqrt{57}}{4} \)

2. Given two functions:

\[ f(x) = 3x + 2, \quad g(x) = x^2 - 1 \]

(a) Find \( f(g(2)) \).

(b) Find the inverse function \( f^{-1}(x) \).

Solution:

(a) Finding \( f(g(2)) \)

First, calculate \( g(2) \):

\[ g(2) = (2)^2 - 1 = 4 - 1 = 3 \]

Now, calculate \( f(g(2)) = f(3) \):

\[ f(3) = 3(3) + 2 = 9 + 2 = 11 \]

Answer: \( f(g(2)) = 11 \)

(b) Finding \( f^{-1}(x) \)

To find the inverse function:

Start with \( y = f(x) \):

\[ y = 3x + 2 \]

Swap \( x \) and \( y \):

\[ x = 3y + 2 \]

Solve for \( y \):

\[ x - 2 = 3y \]

\[ y = \frac{x - 2}{3} \]

Answer: \( f^{-1}(x) = \frac{x - 2}{3} \)

(more examples and explanations coming soon)

Previous
Previous

The Sine Rule: when to use it and how to do the hard questions

Next
Next

How to do sin, cos, tan and use the right one in the exam